Terpenes-Modified Lipid Nanosystems for Temozolomide, Improving Cytotoxicity against Glioblastoma Human Cancer Cells In Vitro - Tatiana N. Pashirova; Andrey V. Nemtarev; Daina N. Buzyurova; Zukhra M. Shaihutdinova; Mudaris N. Dimukhametov; Vasily M. Babaev; Alexandra D. Voloshina; Vladimir F. Mironov (Nanomaterials, 2023)
Currently, increasing the efficiency of glioblastoma treatment is still an unsolved problem. In this study, a combination of promising approaches was proposed: (i) an application of nanotechnology approach to create a new terpene-modified lipid system (7% w/w), using soybean L-α-phosphatidylcholine, N-carbonyl-methoxypolyethylene glycol-2000)-1,2-distearoyl-sn-glycero-3-phosphoethanolamine for delivery of the chemotherapy drug, temozolomide (TMZ, 1 mg/mL); (ii) use of TMZ associated with natural compounds—terpenes (1% w/w) abietic acid and Abies sibirica Ledeb. resin (A. sibirica). Different concentrations and combinations of terpene–lipid systems were employed to treat human cancer cell lines T 98G (glioblastoma), M-Hela (carcinoma of the cervix) and human liver cell lines (Chang liver). The terpene–lipid systems appeared to be unilamellar and of spherical shape under transmission electron microscopy (TEM). The creation of a TMZ-loaded terpene–lipid nanosystem was about 100 nm in diameter with a negative surface charge found by dynamic light scattering. The 74% encapsulation efficiency allowed the release time of TMZ to be prolonged. The modification by terpenes of TMZ-loaded lipid nanoparticles improved by four times the cytotoxicity against human cancer T 98G cells and decreased the cytotoxicity against human normal liver cells. Terpene-modified delivery lipid systems are of potential interest as a combination therapy.